(→Erratum) |
(→Known errors in our work) |
||
Line 3: | Line 3: | ||
== Erratum == | == Erratum == | ||
− | === Generation of a two-photon state from a quantum dot in a microcavity | + | === (2011) Generation of a two-photon state from a quantum dot in a microcavity === |
+ | |||
+ | [http://iopscience.iop.org/1367-2630/13/11/113014/ New J. Phys. 13, 113014 (2011)] | ||
In page 8, last paragraph the equation $$L_\mathrm{I}+L_\mathrm{II}\approx2\langle a^{\dagger2}a^2\rangle$$ should read $$L_\mathrm{I}+L_\mathrm{II}\approx2\int_0^{\infty}dt\,\langle a^{\dagger2}a^2\rangle(t)$$ as the dynamics are always time integrated. | In page 8, last paragraph the equation $$L_\mathrm{I}+L_\mathrm{II}\approx2\langle a^{\dagger2}a^2\rangle$$ should read $$L_\mathrm{I}+L_\mathrm{II}\approx2\int_0^{\infty}dt\,\langle a^{\dagger2}a^2\rangle(t)$$ as the dynamics are always time integrated. | ||
− | === Regimes of strong light-matter coupling under incoherent excitation | + | === (2011) Regimes of strong light-matter coupling under incoherent excitation === |
+ | |||
+ | [http://pra.aps.org/abstract/PRA/v84/i4/e043816 Phys. Rev. A 84, 043816 (2011)] | ||
An $i$ is missing in Eq. (10c), so these coefficient should read: | An $i$ is missing in Eq. (10c), so these coefficient should read: | ||
Line 13: | Line 17: | ||
$$L_{\pm}+iK_\pm=\frac{\frac{8\Omega_\mathrm{L}^2}{\gamma_\sigma(\gamma_\sigma+\gamma_\phi)}\big[1 \pm i \frac{5\gamma_\sigma-\gamma_\phi}{4 R_\mathrm{L}}\big]-\frac{\gamma_\sigma-\gamma_\phi}{\gamma_\sigma+\gamma_\phi}\big[1\pm i\frac{\gamma_\sigma-\gamma_\phi}{4R_\mathrm{L}}\big]}{4\big(1+\frac{8 \Omega_\mathrm{L}^2}{\gamma_\sigma(\gamma_\sigma+\gamma_\phi)}\big)}$$ | $$L_{\pm}+iK_\pm=\frac{\frac{8\Omega_\mathrm{L}^2}{\gamma_\sigma(\gamma_\sigma+\gamma_\phi)}\big[1 \pm i \frac{5\gamma_\sigma-\gamma_\phi}{4 R_\mathrm{L}}\big]-\frac{\gamma_\sigma-\gamma_\phi}{\gamma_\sigma+\gamma_\phi}\big[1\pm i\frac{\gamma_\sigma-\gamma_\phi}{4R_\mathrm{L}}\big]}{4\big(1+\frac{8 \Omega_\mathrm{L}^2}{\gamma_\sigma(\gamma_\sigma+\gamma_\phi)}\big)}$$ | ||
− | === Anticrossing in the PL spectrum of light-matter coupling under incoherent continuous pumping | + | === (2010) Anticrossing in the PL spectrum of light-matter coupling under incoherent continuous pumping === |
+ | |||
+ | [http://www.sciencedirect.com/science/article/pii/S0749603609001219 Superlattices and Microstructures 47, 16 (2010)] | ||
A minus sign is missing in Eq. (3), it should read: | A minus sign is missing in Eq. (3), it should read: | ||
Line 19: | Line 25: | ||
$$\Delta \omega_O=2g\Re\Big\{\sqrt{\sqrt{\Big(1+\frac{P_b}{P_a}\Big)^2-4\frac{\Gamma_+}{g}\Big(-\frac{\Gamma_b}{2g}+\frac{P_b}{P_a}\frac{\Gamma_-}{g}\Big)}-\frac{P_b}{P_a}-\Big(\frac{\Gamma_b}{2g}\Big)^2}\Big\}$$ | $$\Delta \omega_O=2g\Re\Big\{\sqrt{\sqrt{\Big(1+\frac{P_b}{P_a}\Big)^2-4\frac{\Gamma_+}{g}\Big(-\frac{\Gamma_b}{2g}+\frac{P_b}{P_a}\frac{\Gamma_-}{g}\Big)}-\frac{P_b}{P_a}-\Big(\frac{\Gamma_b}{2g}\Big)^2}\Big\}$$ | ||
− | === Microcavity Quantum Electrodynamics (VDM Verlag | + | === (2009) Microcavity Quantum Electrodynamics (VDM Verlag) === |
New J. Phys. 13, 113014 (2011)
In page 8, last paragraph the equation $$L_\mathrm{I}+L_\mathrm{II}\approx2\langle a^{\dagger2}a^2\rangle$$ should read $$L_\mathrm{I}+L_\mathrm{II}\approx2\int_0^{\infty}dt\,\langle a^{\dagger2}a^2\rangle(t)$$ as the dynamics are always time integrated.
Phys. Rev. A 84, 043816 (2011)
An $i$ is missing in Eq. (10c), so these coefficient should read:
$$L_{\pm}+iK_\pm=\frac{\frac{8\Omega_\mathrm{L}^2}{\gamma_\sigma(\gamma_\sigma+\gamma_\phi)}\big[1 \pm i \frac{5\gamma_\sigma-\gamma_\phi}{4 R_\mathrm{L}}\big]-\frac{\gamma_\sigma-\gamma_\phi}{\gamma_\sigma+\gamma_\phi}\big[1\pm i\frac{\gamma_\sigma-\gamma_\phi}{4R_\mathrm{L}}\big]}{4\big(1+\frac{8 \Omega_\mathrm{L}^2}{\gamma_\sigma(\gamma_\sigma+\gamma_\phi)}\big)}$$
Superlattices and Microstructures 47, 16 (2010)
A minus sign is missing in Eq. (3), it should read:
$$\Delta \omega_O=2g\Re\Big\{\sqrt{\sqrt{\Big(1+\frac{P_b}{P_a}\Big)^2-4\frac{\Gamma_+}{g}\Big(-\frac{\Gamma_b}{2g}+\frac{P_b}{P_a}\frac{\Gamma_-}{g}\Big)}-\frac{P_b}{P_a}-\Big(\frac{\Gamma_b}{2g}\Big)^2}\Big\}$$